Distribution of pseudoexfoliation material on anterior segment structures in human autopsy eyes after cataract surgery with intraocular lens implantation - Schmack, Ingo; Auffarth, Gerd U. (International ophthalmology, 2016)
The purpose of the study was to evaluate the distribution and amount of pseudoexfoliation material (PXM) on anterior segment structures in pseudophakic human autopsy eyes with pseudoexfoliation (PEX) syndrome and to study its impact on fixation and decentration of posterior chamber intraocular lenses (IOLs).
Published online: 26 August 2015
Gesehen am 15.05.2020